Limitation of Gaze - Backman, Howard A (Canadian Journal of Optometry, 1980)
Limitations of gaze may be congenital or acquired. The Optometrist should differentiate the two and look for associated anomalies. Some neurologic and congenital oculomotor anomalies are discussed.